ANALISIS EFISIENSI TEKNIS PENGELOLAAN TANAMAN TERPADU (PTT) PADI SAWAH DI PROVINSI BALI - SUHARYANTO, SUHARYANTO; MULYO, JANGKUNG HANDOYO; DARWANTO, DWIDJONO HADI; WIDODO, SRI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
The research of technical efficiency analysis on rice Integrated Crop Management (ICM) in Bali Province had been conducted in three districts (Tabanan, Buleleng and Gianyar) involving 122 farmer samples. Simple random sampling tecnique was used to select farmer samples in two crop seasons during 2011 (wet and dry season). The research was focused to: (1) the level of technical efficiency in rice with ICM approach and (2) to analyze factors influencing its technical efficiency.